S-Assimilation Influences in Carrageenan Biosynthesis Genes during Ethylene-Induced Carposporogenesis in Red Seaweed Grateloupia imbricata - Diana del Rosario-Santana; Rafael R. Robaina; Pilar Garcia-Jimenez (Marine Drugs, 2022)
The synthesis of cell-wall sulfated galactans proceeds through UDP galactose, a major nucleotide sugar in red seaweed, whilst sulfate is transported through S-transporters into algae. Moreover, synthesis of ethylene, a volatile plant growth regulator that plays an important role in red seaweed reproduction, occurs through S-adenosyl methionine. This means that sulfur metabolism is involved in reproduction events as well as sulfated galactan synthesis of red seaweed. In this work we study the effects of methionine and MgSO4 on gene expression of polygalactan synthesis through phosphoglucomutase (PGM) and galactose 1 phosphate uridyltransferase (GALT) and of sulfate assimilation (S-transporter and sulfate adenylyltransferase, SAT) using treatment of ethylene for 15 min, which elicited cystocarp development in Grateloupia imbricata. Also, expressions of carbohydrate sulfotransferase and galactose-6-sulfurylase in charge of the addition and removal of sulfate groups to galactans backbone were examined. Outstanding results occurred in the presence of methionine, which provoked an increment in transcript number of genes encoding S-transporter and assimilation compared to controls regardless of the development stage of thalli. Otherwise, methionine diminished the transcript levels of PGM and GALT and expressions are associated with the fertilization stage of thalli of G. imbricata. As opposite, methionine and MgSO4 did not affect the transcript number of carbohydrate sulfotransferase and galactose-6-sulfurylase. Nonetheless, differential expression was obtained for sulfurylases according to the development stages of thalli of G. imbricata.